Evaluasi Dampak Program Penyediaan Air Minum dan Sanitasi Berbasis Masyarakat (PAMSIMAS) di Kecamatan Kutowinangun Kabupaten Kebumen - Windriyaningrum, Rasika Istahara; Purnaweni, Hartuti; Kismartini, Kismartini (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
The problem that occur in Kutowinangun, Kebumen related with Third Water Supply And Sanitation For Low-Income Communities Project (WSLIC-3 or PAMSIMAS) is many people in these location is difficult to get clean water. Beside of that, the people also don’t understand how to a good sanitation is, because there are still many people who do not reflect the behavior of a healthy lifestyle, such as defecation, so that rates of diarrhea is still quite high. The purpose of this study is to identify and analyze the social impacts and factors affecting WSLIC-3 or PAMSIMAS Program. Data is collected with interviews and observations technique, and processed and analyzed qualitatively. The result showed that social impact perceived by the people after WSLIC-3 or PAMSIMAS program applied is more the people feel more convenient and easier to access clean water and sanitation, improve self-awareness of children from an early age to have a clean and healthy behaviors supported by sanitation facilities in schools, as well as an improvement of hygienic and healthy behavior, although the impact has not been fully felt by the entire people yet. This is due to several factors affecting the mindset of the people who still rely on government assistance, economic constraints, and the negligence of the operator. The suggestion of this research is the need for intensive guidance to the people to apply a clean and healthy lifestyle, as well as regular monitoring of physical facilities.